A Light Sensitive Nanogenerator for Self‐Powered UV Detection with Two Measuring Ranges. Issue 1 (27th October 2016) - Cheng, Li; Zheng, Youbin; Xu, Qi; Qin, Yong
Abstract : An integrated UV sensor with two measuring ranges for self‐powered UV light detection is fabricated, which itself can simultaneously harvest the mechanical energy from the environment and quantitatively detect the intensity of UV light as a self‐powered sensor without any storage circuit or external measurement instruments. This work contributes towards the development and application of nanogenerators and self‐powered nanosystems.